A phage-encoded counter-defense inhibits an NAD-degrading anti-phage defense system. - Christian L Loyo; Alan D Grossman (PLoS Genetics)
Bacteria contain a diverse array of genes that provide defense against predation by phages. Anti-phage defense genes are frequently located on mobile genetic elements and spread through horizontal gene transfer. Despite the many anti-phage defense systems that have been identified, less is known about how phages overcome the defenses employed by bacteria. The integrative and conjugative element ICEBs1 in Bacillus subtilis contains a gene, spbK, that confers defense against the temperate phage SPβ through an abortive infection mechanism. Using genetic and biochemical analyses, we found that SpbK is an NADase that is activated by binding to the SPβ phage portal protein YonE. The presence of YonE stimulates NADase activity of the TIR domain of SpbK and causes cell death. We also found that the SPβ-like phage Φ3T has a counter-defense gene that prevents SpbK-mediated abortive infection and enables the phage to produce viable progeny, even in cells expressing spbK. We made SPβ-Φ3T hybrid phages that were resistant to SpbK-mediated defense and identified a single gene in Φ3T (phi3T_120, now called nip for NADase inhibitor from phage) that was both necessary and sufficient to block SpbK-mediated anti-phage defense. We found that Nip binds to the TIR (NADase) domain of SpbK and inhibits NADase activity. Our results provide insight into how phages overcome bacterial immunity by inhibiting enzymatic activity of an anti-phage defense protein.